Edukasi Kesehatan Mengenai Aktivitas Olahraga dan Pola Istirahat Bagi Wanita Usia Dewasa dan Lansia - Didik Rilastiyo Budi; Arfin Deri Listiandi; Neva Widanita; Dewi Anggraeni (Pusat Kajian Pendidikan Olahraga, Kesehatan dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Uiveristas Negeri Padang Jl. Prof. Hamka, Air Tawar Padang 25131 Telp. 0751-7059901, 2020)
Community Service Activities (PKM) aim to provide education and training to community members in Central Sokaraja Village, Sokaraja District, Banyumas Regency, especially for women aged 30-60 years regarding the importance of doing regular sports activities and implementing a good sleep rest pattern for maintain and even improve body health. The PKM method uses a seminar and training approach. The seminar was conducted by providing knowledge and understanding material to the participants, while the training method was carried out by the participants and the resource persons doing direct practice in carrying out health sports activities. The response given by the service partners is very good, so that this service activity can be carried out smoothly with a total of 43 participants. The results obtained, overall the training participants have carried out regular health sports activities but do not yet have a good sleep rest pattern, so the advice that can be given is that there is a need to increase understanding in the practice of sleeping rest patterns so that the health and fitness of the community is getting better .